Commentary: COVID-19 in cardiac surgery – we are still learning and have yet to see all possible covid-19 complications (2020)
The novel coronavirus outbreak in Wuhan, China, led to over 31 million infected and nearly a million deaths 1,2. Coronavirus Disease 2019 (COVID 19), is characterized by extreme virulence and a complex spectrum of pathologies ranging in severity from mild to multi-organ failure3 and death. Over the past nine months, our knowledge of the pathophysiology and extrapulmonary manifestations of COVID-19 has grown tremendously. Yet, despite this, we are constantly discovering new manifestations such as the development of a hypercoagulable state4-6 . With an anxious global community focused upon the development of a novel vaccine, it’s easy to overlook that unique and potentially fatal complications are yet to be identified.